Odpowiedzi

2010-03-18T15:20:50+01:00
W załączniku masz skan odp
Najlepsza Odpowiedź!
2010-03-18T15:28:46+01:00
A) 7x² − 4x − 6x² + 4 − x² + 5x =
=x+4
b) −2(3a − 2b) − 4a(2 − 3a + 2b) =
=-6a+4b-8a+12a²-2ab=12a2 − 8ab − 14a + 4b
c) (4 − x)(2x + 5) − 4 =
=8x+20-2x²-5=−2x² + 3x + 16
d) (4 − 2x)(3x − 3) − 2x(3x + 1) =
=12x-12-6x²+6=−12x² + 16x − 12
5x⁵(2x³y⁴)²÷25(x³y)³xy⁶=5x⁵(2x⁶y⁸)÷25(x⁹y³)xy⁶=10x³⁰y⁸÷25x⁹y³*xy⁶=111
dla x = 555 i y = 4
{4(2x + 3) − 2(4y − 1) = 30
{(5x+1)÷3-(y-3)÷4=3
{8x+12-8y+2=30
{(5x+1÷3)-(y+3÷4)=3/*12
{8x=16+8y/÷8
{20x+4-3y+9=36
{x=2+y
{20(2+y)+4-3y+9=36
{x=2+y
{40+20y+4-3y+9=36
{x=2+y
{17y=-17/*(-1)
{x=2+y
{y=-1
{x=1
1 5 1